Improving advance care planning for care home residents with dementia: Evaluation of simulation training for care home workers. (April 2020) - Katwa, Asha Pari; Jenner, Chris; MacDonald, Karen; Barnett, Nina
The importance of effective advance care planning is often underestimated by professionals caring for care home residents. Using a simulated scenario, this model aimed to highlight the importance of timely advance care planning for care home residents. An adapted simulation effectiveness tool was used to evaluate a simulated scenario of a resident with advanced dementia. Feedback from this tool, N = 28 (response rate 82%), suggests this model was well received and that simulation training delivered by a multi-professional faculty, effectively demonstrates the benefits of early advance care planning for residents with dementia.